Ilaser Submucous Destruction in the Treatment of Hemorrhoids - S. A. Frolov; D. V. Vyshegorodtsev; A. M. Kuzminov; Yu. L. Trubacheva; V. Yu. Korolik; I. S. Bogormistrov; I. A. Mukhin; A. N. Ryndin; A. A. Anarbaeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to improve the results of treatment in patients with hemorrhoids of the 2nd and 3rd stages.Materials and methods. The prospective study included 60 patients with hemorrhoids of the 2nd and 3rd stages. All patients underwent destruction of internal hemorrhoids with a fiber laser with a diode pump with a wavelength of 1940 nm. The technique is based on the effect of laser energy on the cavernous tissue of the internal hemorrhoidal node and on the terminal branches of the upper rectal artery. The efficiency of the destruction of internal hemorrhoids and the frequency of relapses of the disease were evaluated. The effectiveness of the proposed method was evaluated using anoscopy, measurement of the size of internal hemorrhoidal nodes, transrectal ultrasound with dopplerography. The analysis of the intensity of the pain syndrome, the consumption of nonsteroidal anti-inflammatory drugs and the assessment of the quality of life on the SF-36 scale was carried out. Sphincterometry was performed in all patients to determine the possible effect of laser radiation on the rectal locking apparatus. To assess the possible causes of complications, a single-factor analysis of the amount of energy transferred to each hemorrhoidal node and the total amount of energy spent on the operation was conducted.Results. In all patients, by day 7 after surgery, the pain syndrome in 43 patients (75.4 %) corresponded to 0 points according to VAS. In 3 patients (5 %) intraoperative hemorrhage developed. In the early postoperative period, 5 patients (8.3 %) had 7 complications: 5 cases of thrombosis of the external hemorrhoidal node and 2 — of acute urinary retention. The conducted single-factor analysis showed the dependence of the development of complications on the energy transferred to each hemorrhoidal node and its total amount for the entire operation. In terms of up to 6 months, there were no signs of a return of the disease in any case (hemorrhoidal prolapse and blood discharge). The detected hemorrhoids before the operation, a month after the operation, were not visualized, which persisted after 6 months. The performed transrectal ultrasound examination with spectral-wave dopplerography for up to 6 months allowed to diagnose a persistent decrease in blood flow along the terminal branches of the upper rectal artery compared with preoperative values. When performed sphincterometry, there was no change in the parameters of the anal sphincter function compared to preoperative parameters.Conclusion. The proposed method applying a fiber laser with a diode pump with a wavelength of 1940 nm makes it possible to affect transdermally the internal hemorrhoidal node without damaging the mucosa of the anal canal. The absence of postoperative wounds in the anal canal leads to a decrease in pain syndrome, and by day 7 there are no clinical manifestations of hemorrhoids. The method of laser destruction of internal hemorrhoids can be used in outpatient conditions and can improve the quality of life of patients in the early postoperative period.